SACRED AND PROFANE IN THE CONCEPTUALIZATION OF TIME: LEXICAL-SEMANTIC ASPECT - Barchuk, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This article deals with lexical-semantic field of time and semantic structure of lexical units. Sacred and profane components of tokens with meaning of time are determined and characterized. The nuclear and peripheral units and features of lexical interpretation of time as the element of modeling world are found out.